PENGARUH POLA DEMOKRASI, BANTUAN DAMAI DAN MINAT BELAJAR TERHADAP KEMAMPUAN BERPIKIR LOGIS ANAK KELOMPOK B - supriyatni, supriyatni; Sarwanto, Sarwanto; Amini, Mukti (UNIVERSITAS SLAMET RIYADI, 2025)
Educational problems in general are often faced by students from the beginning of school, they often find it difficult to adjust to their environment, teachers, school rules, friends at school and so on. This study aims to determine the interaction of democratic parenting, peer assistance, and interest in learning partially or together on the logical thinking ability of students in Group B Kindergarten Gugus Anggrek, Jaten District.This study uses a quantitative design with an emphasis on explanation (explanatory research). The population consisted of all guardians of students and kindergarten students from the Orchid cluster, Jaten District, Karanganyar Regency which consisted of 5 kindergarten institutions. The sample is 45 kindergarten students in group B, with n random methods. The questionnaire instrument was first tested for validity and reliability on students other than respondents. Data analysis technique using Multiple Linear Regression test. The results showed that partially democratic parenting and interest had a positive and significant effect, while peer assistance had a positive but not significant effect on logical thinking ability. Simultaneously, the three variables have a positive and significant impact on logical thinking skills